Non-Oscillatory Power Spectrum From States of Low Energy in Kinetically Dominated Early Universes - Martín-Benito , Mercedes; Neves , Rita B.; Olmedo , Javier (Frontiers in Astronomy and Space Sciences, 2021)
Recently, States of Low Energy (SLEs) have been proposed as viable vacuum states of primordial perturbations within Loop Quantum Cosmology (LQC). In this work we investigate the effect of the high curvature region of LQC on the definition of SLEs. Shifting the support of the test function that defines them away from this regime results in primordial power spectra of perturbations closer to those of the so-called Non-oscillatory (NO) vacuum, which is another viable choice of initial conditions previously introduced in the LQC context. Furthermore, through a comparison with the Hadamard-like SLEs, we prove that the NO vacuum is of Hadamard type as well.